A new device to simulate the performance of rubber dams for dental applications. (February 2021) - Santos, Amara Eulália Chagas; Linhares, Felipe Nunes; Leite, Marcia Christina Amorim Moreira; Escócio, Vivane Alves; Nunes, Regina Célia Reis
Abstract: Rubber dams employed for endodontic treatment are commonly based on natural rubber latex compounds and it is essential that they remain unbroken throughout the different procedures. The in-use failure of some types of rubber dams can be related to the time spent under tension in contact with saliva and/or to sodium hypochlorite. Five different types of commercial rubber dams were assessed with respect to physico-mechanical properties (crosslink density, stress at break, tear strength and stress relaxation), morphological aspects (Scanning Electron Microscopy), and elemental analyses (energy-dispersive X-ray spectrometry). Moreover, a special bench apparatus was developed to mimic actual conditions of rubber dams during endodontic procedures. Results showed that the device performance was reliable and comparable to observations during clinical activity corroborated by the stress relaxation test. Samples based on sulfur curing system with predominance of accelerator has better performance under stress relaxation tests than those samples with higher concentration of sulfur. Highlights: A simple device was developed to assess rubber dams for dentistry application. Sodium hypochlorite affected the mechanism of stress relaxation process. The curing system affected the stress relaxation properties of the rubber dams.